Якшур-Бодья - сердцу милый уголок: 1929-1999 / [составитель В. Н. Иванова] - Иванова Валентина Никоноровна (1999)
Экземпляры: АБ (20170109) / Инвентарный номер: 33120 / Цена: 30.00 / Сис.шифр: 63.3(2Рос-6Удм) / Авт.знак: Я 50 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)